The Art of Leading -Some Random Thoughts - Jaiswal, Girish (Gyan Management Journal, 2010)
Who is a leader? Can the leadership qualities be developed in any individual through training? What is the relationship between a leader and a manager? Do the managers need to possess strong leadership qualities etc: are some of the questions which often agitate the mind? The article looks for the answers to these very questions in a simple way.
Keywords: leader; leadership; manager; qualities